Profil Kelembagaan Desa Di Desa Buluh Cina Kecamatan Siak Hulu Kabupaten Kampar Tahun 2010 - Isril; Raja Amin; Adlin (Nakhoda: Jurnal Ilmu Pemerintahan, 2011)
Village govenment institutionalism and BPD that have formed by Rules of Government nomor 72 year of2005. Buluh Cina village are tourism village that have much potention and need to get support fromvillage institutionalism to create a potentions for positively effect for society. But a conditions society inBuluh Cina village are not support and it make a institutionalism in buluh Cina village doesnt havecapability to protect the society. This research describes the profil of government of village, BadanPemusyawaratan Desa and Lembaga Permusyawaratan Desa in Buluh Cina Village that have use a rulesof government inform educational of elite in institutionalism village. This research purpose to analize theinstitutionalism in Buluh Cina village with the rules of government and also describe the educational invillage. Kualitative descriptive methods with study literatur based on documents and also interview withinforman that choice by purpossive sampling. This research show that government institutionalism inBuluh Cina Village are have done form based on rules government but educational elite 60%, under SLTPand BPD also formed by rules of government and educational of BPD are 40% are Strata 1. LembagaPemberdayaan masyarakat (LPM) in Buluh Cina are not same with the Perda Kampar Regency andperson in LPM are under SLTP.